How to Find Gap Analysis in Undergraduate User Satisfaction Through a Tracer Study - Nerisafitra, Paramitha; Martini Dwi Endah Susanti; Ronggo Alit; Aditya Prapanca (Universitas Nahdlatul Ulama Surabaya, 2023)
Undergraduate alumni play a crucial role in shaping the educational process at higher education institutions. Therefore, it is essential to continuously assess the satisfaction of graduate users to gauge their level of contentment. This research aims to measure graduate user satisfaction through gap analysis by comparing user expectations with the actual performance of graduates based on the five dimensions of the SERVQUAL model. The study combines the Customer Satisfaction Index (CSI), which calculates satisfaction gaps, with Importance-Performance Analysis (IPA), used to map the five dimensions of service quality and prioritize improvements. The results indicate that the graduate user satisfaction index is 78%, placing it in the